Therapeutic efficacy of acupuncture point stimulation for stomach cancer pain: a systematic review and meta-analysis - Zhou, Xuancheng; Zhang, Jieying; Jiang, Lai; Zhang, Shengke; Gu, Yuheng; Tang, Jingyi; Pu, Tong; Quan, Xiaomin; Chi, Hao; Huang, Shangke (Frontiers in Neurology, 2024)
Purpose:In recent years,traditional chinese medicine has received widespread attention in the field of cancer pain treatment.This meta-analysis is the first to evaluate the effectiveness and safety of acupuncture point stimulation in the treatment of stomach cancer pain.Methods:For this systematic review and meta-analysis, we searched PubMed, Web of Science, Cochrane Library, Embase, WANFANG, China National Knowledge Infrastructure (CNKI), and Chinese Journal of Science and Technology (VIP) databases as well as forward and backward citations to studies published between database